CdS / BiOBr composite nanofiber photocatalyst and preparation method thereof

By fixing BiOBr inside the nanofiber and forming a composite nanofiber photocatalyst with CdS/BiOBr heterojunction, the existing photocatalyst recovery and operating conditions are solved, and efficient industrial wastewater treatment and photocatalytic reaction efficiency are achieved.

CN119236975APending Publication Date: 2025-01-03CHINA SHENHUA COAL TO LIQUID & CHEM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411309957.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In industrial wastewater treatment, existing photocatalysts have problems such as difficult to recover powdered materials, easy to agglomerate and harsh operating conditions, resulting in limited use in practical applications.

Method used

By fixing BiOBr inside the nanofiber and forming a composite nanofiber photocatalyst using a continuous ion layer adsorption reaction method, a long-term high-temperature hydrothermal reaction is avoided, and the reusability and photocatalytic activity of the material are improved.

Benefits of technology

It has achieved efficient photocatalytic activity improvement and material stability, reduced agglomeration phenomenon, improved the adsorption capacity of dyes and difficult-to-degrade organic pollutants in industrial wastewater, and enhanced the photocatalytic reaction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236975A_ABST
    Figure CN119236975A_ABST
Patent Text Reader

Abstract

The invention provides a CdS / BiOBr composite nanofiber photocatalyst and a preparation method of the CdS / BiOBr composite nanofiber photocatalyst. In the CdS / BiOBr composite nanofiber photocatalyst, BiOBr nano-particles are loaded in nanofibers and / or on the surfaces of the nanofibers, CdS nano-particles are formed at the exposed BiOBr positions of the surfaces of the nanofibers, and the BiOBr nano-particles and the CdS nano-particles form CdS / BiOBr heterojunctions. Heterojunctions formed by the CdS / BiOBr composite nanofiber photocatalyst are firmly combined with nanofibers, the carrier separation efficiency of the catalyst can be effectively improved, so that higher photocatalytic activity is achieved, meanwhile, the CdS / BiOBr composite nanofiber photocatalyst has a large specific surface area, adsorption of dyes and refractory organic pollutants in industrial wastewater can be greatly improved, and the photocatalytic activity is improved. Meanwhile, agglomeration of the CdS / BiOBr photocatalyst is reduced, and more active sites are provided in a photocatalytic reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional nanomaterials and photocatalytic materials, and specifically relates to a method for preparing a CdS / BiOBr composite nanofiber photocatalyst. The CdS / BiOBr composite nanofiber material can be applied to the degradation of dyes and refractory organic pollutants, sewage treatment and other fields. Background Art

[0002] Industrial wastewater has the characteristics of large water quality changes, high content of organic pollutants, and high salt content, and is difficult to treat. The organic pollutants contained in industrial wastewater are mostly nitrogen-containing and oxygen-containing heterocyclic compounds, many of which have chromogenic groups, which makes the chromaticity of industrial wastewater high, and the chemical oxygen demand (COD) can reach 2000-20000 mg / L. Traditional sewage treatment methods include physical, biological and chemical methods. Among them, physical treatment mainly uses activated carbon adsorption, but the treatment capacity is limited due to the influence of adsorption capacity, and there is a problem of adsorbent regeneration; biological methods mainly use aerobic-anaerobic microbial metabolism to degrade pollutants, but the organic pollutants in industrial wastewater are complex and have strong biological toxicity, resulting in unstable effluent and difficult to meet standards; chemical treatment mainly uses catalytic methods to produce a large number of active free radicals to degrade organic pollutants and is widely used, especially the use of photocatalysts to photocatalytically degrade industrial wastewater, which can reduce the use of chemical reagents and has high decolorization efficiency for wastewater.

[0003] At present, the photocatalysts used for industrial wastewater treatment are mainly powdered. Powdered photocatalysts are difficult to recycle and easy to agglomerate, which limits the use of photocatalysts in actual sewage treatment. Electrospun nanofiber membranes have the characteristics of large specific surface area, strong adsorption capacity and adjustable structural properties. They are ideal photocatalyst immobilization carrier materials and can solve the problems faced by powdered photocatalysts. BiOBr is a new type of layered semiconductor material with good visible light response, and the single-component BiOBr can be improved by constructing a heterojunction, which effectively promotes the separation of photogenerated carriers and improves the photocatalytic activity. In the existing nanofiber preparation technology for photocatalysis, either a heterojunction is not constructed to improve the photocatalytic activity (such as CN 117661192A), or two long-term high-temperature hydrothermal reactions are required to respectively separate BiOBr and W. 18 O 49 It is fixed on the surface of nanofibers to form a heterojunction, and the operating conditions are harsh and there are many steps (such as CN 115779973A). Summary of the invention

[0004] The purpose of the present invention is to overcome the defects and problems of the above-mentioned prior art methods, and to provide a CdS / BiOBr composite nanofiber photocatalyst and a preparation method thereof. In the preparation method, a composite nanofiber photocatalyst of CdS / BiOBr heterojunction is formed by fixing BiOBr inside the nanofiber and forming a CdS / BiOBr heterojunction on the surface of the nanofiber through a continuous ion layer adsorption reaction (SILAR) method. More specifically, a polymer is first added to a solution of synthesized BiOBr nanoparticles to form a spinning solution, and nanofibers are prepared by electrospinning, wherein the BiOBr nanoparticles are embedded in the polymer nanofibers; then, through a continuous ion layer adsorption reaction (SILAR) method, the collected nanofiber membrane is sequentially immersed in a cadmium acetate solution, deionized water, a sodium sulfide solution, and deionized water and circulated a certain number of times, CdS nanoparticles are precipitated and grown on the outer surface of the nanofiber, and a CdS / BiOBr heterojunction is formed on the surface of the nanofiber to obtain a CdS / BiOBr composite nanofiber photocatalyst. The SILAR method for preparing semiconductor heterojunctions is simple to operate, low in cost and highly efficient. This method can efficiently form CdS / BiOBr heterojunctions and firmly combine them with nanofibers, avoiding long-term high-temperature hydrothermal reactions. While improving the activity of composite nanofiber photocatalysts, it also improves the reusability of the material and lowers the preparation threshold.

[0005] According to a first aspect of the present invention, a CdS / BiOBr composite nanofiber photocatalyst is provided, wherein BiOBr nanoparticles are loaded inside the nanofibers and / or on the surface of the nanofibers, CdS nanoparticles are formed at the BiOBr exposed on the surface of the nanofibers, and the BiOBr nanoparticles and the CdS nanoparticles form a CdS / BiOBr heterojunction.

[0006] BiOBr nanoparticles loaded inside nanofibers means that BiOBr nanoparticles are basically embedded in the nanofibers, but a small part of the surface is still exposed; BiOBr nanoparticles partially loaded on the surface of nanofibers means that a part of BiOBr nanoparticles is embedded or attached to the nanofibers, and most of the surface area is exposed.

[0007] Preferably, the diameter of the BiOBr nanoparticles is 200 nm to 2 μm.

[0008] Preferably, the diameter of the CdS nanoparticles is 200 nm to 10 μm.

[0009] Preferably, the diameter of the nanofibers is 500 nm to 5 μm.

[0010] Preferably, the nanofibers are polyvinylidene fluoride nanofibers or polyacrylonitrile nanofibers.

[0011] Preferably, relative to the total weight of the CdS / BiOBr composite nanofiber photocatalyst, the weight ratio of the BiOBr nanoparticles is 2% to 30%, and the weight ratio of the CdS nanoparticles is 0.5% to 50%.

[0012] Preferably, the CdS / BiOBr composite nanofiber photocatalyst is in the form of a nanofiber film.

[0013] Preferably, the thickness of the nanofiber membrane is 500 nm to 50 μm.

[0014] According to a second aspect of the present invention, there is provided a method for preparing the CdS / BiOBr composite nanofiber photocatalyst according to the present invention, comprising the following steps:

[0015] (1) dissolving a bismuth salt in an organic solvent to prepare a solution A, and dissolving a bromide in deionized water to prepare a solution B; then, mixing the solution A and the solution B to obtain a mixed reaction system, and stirring to generate BiOBr nanoparticles; adding a polymer thereto, and stirring and mixing to form a transparent, viscous, and homogeneous spinning solution;

[0016] (2) spinning the spinning solution obtained in step (1) to obtain a BiOBr nanofiber membrane;

[0017] (3) Dissolving cadmium salt in deionized water to prepare solution C, and adjusting the pH value to 3-6; dissolving sodium sulfide in deionized water to prepare solution D, and adjusting the pH value to 10-12; using solution C and solution D to precipitate and grow CdS nanoparticles on the BiOBr nanofiber membrane through a continuous ionic layer adsorption reaction (SILAR) method to obtain a CdS / BiOBr composite nanofiber photocatalyst.

[0018] Preferably, the volume ratio of solution A to solution B forming the mixed reaction system is 20:1 to 100:1.

[0019] Preferably, the molar ratio of Bi in solution A to Br in solution B forming the mixed reaction system is 1:1.

[0020] Preferably, the molar concentration of Bi in solution A is 0.005 to 1 mol / L.

[0021] Preferably, the molar concentration of Br in solution B is 0.1 to 10 mol / L.

[0022] Preferably, the bismuth salt is one or more selected from bismuth nitrate, bismuth chloride, bismuth citrate, bismuth salicylate, bismuth acetate and bismuth oxalate.

[0023] Preferably, the bromide is one or more selected from potassium bromide or sodium bromide.

[0024] Preferably, the organic solvent is an organic solvent miscible with water, and more preferably, the organic solvent is N,N-dimethylformamide or N,N-dimethylacetamide.

[0025] Preferably, the polymer is polyvinylidene fluoride or polyacrylonitrile.

[0026] Preferably, the content of the polymer is 8 wt% to 20 wt% relative to the total weight of the spinning solution.

[0027] Preferably, the method steps in step (2) are as follows:

[0028] The spinning solution is added into a syringe and connected to the electrospinning needle through a pipeline. The positive electrode of the high-voltage power supply is connected to the electrospinning needle as the spinning end. The ground electrode of the high-voltage power supply is connected to a rotating roller covered with aluminum foil as the receiving end. A micro-injection pump is used to control the flow rate of the spinning solution, and voltage is applied for electrospinning. The BiOBr nanofiber membrane is collected at the receiving end.

[0029] Preferably, in step (2), the flow rate of the spinning solution is 0.5-2 mL / h; the spinning voltage is 10-25 kV, the distance between the spinning end and the receiving end is 10-30 cm; and the rotation speed of the rotating roller is 100-2000 rpm.

[0030] Preferably, the cadmium salt is selected from cadmium acetate, cadmium chloride and cadmium nitrate.

[0031] Preferably, the molar concentration of cadmium in solution C is 0.05 to 0.2 mol / L.

[0032] Preferably, the molar concentration of the sodium sulfide solution is 0.025 to 0.2 mol / L.

[0033] The reagent for adjusting the pH of solution C is an acid commonly used in the art, such as hydrochloric acid, acetic acid, sulfuric acid, and the like.

[0034] The reagent for adjusting the pH of solution D is an alkaline solution commonly used in the art, for example, sodium hydroxide solution, potassium hydroxide solution, ammonia solution, etc.

[0035] Preferably, the operation steps of the continuous ionic layer adsorption reaction (SILAR) method in step (3) are:

[0036] (a) immersing the BiOBr nanofiber membrane obtained in step (2) into solution C to adsorb cadmium ions on the surface for 30 to 180 seconds;

[0037] (b) taking out the BiOBr nanofiber membrane and immersing it in deionized water for cleaning, preferably immersing it in 50 to 500 mL of deionized water for cleaning for 30 seconds;

[0038] (c) The BiOBr nanofiber membrane was taken out and immersed in solution D for in situ growth of CdS for 30 to 180 s;

[0039] (d) taking out the BiOBr nanofiber membrane and immersing it in unused deionized water for cleaning, preferably immersing it in unused 50 to 500 mL of deionized water for cleaning for 30 seconds;

[0040] (e) The above four steps (a) to (d) are performed sequentially as one cycle, and the number of cycles is 3 to 50 times, which can be adjusted according to needs to obtain a CdS / BiOBr composite nanofiber photocatalyst.

[0041] The present invention prepares the CdS / BiOBr composite nanofiber photocatalyst by electrospinning technology and continuous ion layer adsorption reaction method, wherein BiOBr is fixed inside and on the surface of the nanofiber, and CdS precipitates and grows on the BiOBr exposed on the surface of the nanofiber to form a heterojunction without the need for long-term high-temperature hydrothermal reaction.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] (1) First, BiOBr nanoparticles are prepared, and then a polymer is added to form a high-viscosity polymer solution, so that the BiOBr nanoparticles are fixed in the spinning solution without agglomeration.

[0044] (2) BiOBr nanoparticles are evenly dispersed in the spinning solution, so that after electrospinning, BiOBr is fixed inside and on the surface of the nanofibers. BiOBr is firmly bonded to the nanofibers, which can improve the service life of the photocatalyst.

[0045] (3) CdS nanoparticles are in situ precipitated and grown at the BiOBr exposed on the surface of the nanofibers by the continuous ionic layer adsorption reaction (SILAR) method to form a CdS / BiOBr heterojunction. The entire preparation process consists of a four-step immersion-cleaning operation. The method is simple, the conditions are mild, and the nanofiber structure will not be destroyed. The formed heterojunction is firmly bonded to the nanofibers, which can effectively improve the catalyst's carrier separation efficiency, thereby achieving higher photocatalytic activity.

[0046] (4) The CdS / BiOBr composite nanofiber photocatalyst constructed by the present invention has a large specific surface area, which can greatly improve the adsorption of dyes and difficult-to-degrade organic pollutants in industrial wastewater, while reducing the agglomeration of CdS / BiOBr photocatalysts, providing more active sites in the photocatalytic reaction. The one-dimensional structure of the nanofiber also facilitates the radial transport and separation of carriers, which helps to improve the efficiency of the photocatalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 Schematic diagram showing the preparation process of CdS / BiOBr composite nanofiber photocatalyst prepared according to Example 1 and Example 2.

[0048] Figure 2 : Shows the X-ray diffraction pattern of the CdS / BiOBr composite nanofiber photocatalyst prepared according to Example 2.

[0049] Figure 3 A scanning electron microscope photograph showing the CdS / BiOBr composite nanofiber photocatalyst prepared according to Example 2.

[0050] Figure 4 The figure shows the catalytic degradation curve of Rhodamine B using the CdS / BiOBr composite nanofiber photocatalyst prepared according to Example 2.

[0051] Figure 5 The bar graph shows the catalytic efficiency (degradation rate of Rhodamine B) of the CdS / BiOBr composite nanofiber photocatalyst prepared according to Example 2 as the number of cycles changes.

[0052] Figure 6 A bar graph showing the photocatalytic efficiency (degradation rate of Rhodamine B) of the CdS / BiOBr composite nanofiber prepared according to Example 2 and the photocatalytic efficiency (degradation rate of Rhodamine B) of the PAN-BiOBr / CdS nanofiber membrane prepared according to Comparative Example 1 as a function of the number of cycles used. DETAILED DESCRIPTION

[0053] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0054] Example 1

[0055] The preparation method of BiOBr / PAN nanofiber membrane is as follows:

[0056] 2.5 mmol Bi(NO3)3·5H2O was dissolved in 20 g N,N-dimethylformamide (DMF) and stirred to obtain a transparent and clear solution A. 2.5 mmol KBr was dissolved in 0.5 mL deionized water to obtain a transparent and clear solution B. Solution A and solution B were mixed, stirred and cooled to room temperature, 3.5 g polyacrylonitrile (PAN) was added to the mixed solution, and the mixture was stirred and mixed to form a transparent, viscous and homogeneous spinning solution, wherein the concentration of the polymer was 14.6 wt% and the particle size of the BiOBr particles was 500 nm.

[0057] The spinning solution was loaded into a plastic syringe for electrospinning with an applied voltage of 15 kV, a needle tip distance of 15 cm from the receiver, a roller speed of 800 rpm, and a syringe pump flow rate of 1.2 mL / h. BiOBr nanofiber membranes with a thickness of 2 μm were collected on the aluminum foil of the receiver.

[0058] Example 2

[0059] The preparation method of CdS / BiOBr composite nanofiber photocatalyst is as follows:

[0060] Prepare 100 mL of 0.1 mol / L cadmium acetate solution, adjust the pH value to 5 with 0.1 M HCl, and use it as solution C. Prepare 100 mL of 0.05 mol / L sodium sulfide solution, adjust the pH value to 12 with 0.1 M NaOH, and use it as solution D. 8 mg of the BiOBr / PAN nanofiber membrane prepared in Example 1 was immersed in solution C for 60 s, taken out and immersed in 100 mL of deionized water for 30 s, then taken out and immersed in solution D for 180 s, and then taken out and immersed in another 100 mL of deionized water for 30 s. The above four immersion-removal operations were performed continuously for 10 times to obtain a CdS / BiOBr composite nanofiber photocatalyst. The size of the CdS nanoparticles was 2 μm.

[0061] Figure 1 Schematic diagram showing the preparation process of CdS / BiOBr composite nanofiber photocatalyst according to Example 1 and Example 2.

[0062] Figure 2 To show the X-ray diffraction pattern of the CdS / BiOBr composite nanofiber photocatalyst prepared according to Example 2, diffraction peaks corresponding to the (101), (110), (112), (200), (211), (212), (220), and (310) crystal planes of CdS / BiOBr were observed at 2θ=25.2°, 32.2°, 39.3°, 46.2°, 53.4°, 57.2°, 67.5°, 76.8°, etc. in the diffraction pattern, proving the successful preparation of the CdS / BiOBr composite nanofiber photocatalyst.

[0063] Figure 3 The SEM image shows the CdS / BiOBr composite nanofiber photocatalyst prepared according to Example 2. Figure 3 It can be clearly observed that CdS grows and deposits on the exposed BiOBr on the surface of the nanofibers to form a CdS / BiOBr heterojunction. It can be seen that the fiber diameter is 1-2 μm, the size of the BiOBr nanoparticles is 500-800 nm, and the size of the CdS nanoparticles is 1-3 μm.

[0064] Example 3

[0065] Dissolve 5mmol of Bi(Ac)3 in 50g of N,N-dimethylacetamide (DMAc) and stir to obtain a transparent and clear solution A. Dissolve 5mmol of KBr in 0.5mL of deionized water to obtain a transparent and clear solution B. Mix solution A and solution B, and cool the solution to room temperature after stirring. Add 8g of polyvinylidene fluoride (PVDF) to the mixed solution, and stir and mix thoroughly to form a transparent, viscous and homogeneous spinning solution. The spinning solution is loaded into a plastic syringe for electrospinning. The applied voltage is 12.5kV, the needle tip is 15cm away from the receiver, the roller speed is 1000RPM, the injection pump flow rate is controlled to be 2.0mL / h, and the BiOBr / PVDF nanofiber membrane is collected on the aluminum foil of the receiver.

[0066] Prepare 500 mL of 0.1 mol / L cadmium acetate solution, adjust the pH value to 3.5 with 0.1 M HCl, and use it as solution C. Prepare 500 mL of 0.1 mol / L sodium sulfide solution, adjust the pH value to 12 with 0.1 M NaOH, and use it as solution D. Immerse 20 mg of BiOBr / PVDF nanofiber membrane in solution C for 30 seconds, take it out and immerse it in 500 mL of deionized water for 15 seconds, then take it out and immerse it in solution B for 60 seconds, take it out and immerse it in another 100 mL of deionized water for 15 seconds. The above four immersion-removal operations were performed continuously for 40 times to obtain CdS / BiOBr composite nanofiber photocatalyst.

[0067] Example 4

[0068] Application of CdS / BiOBr composite nanofiber photocatalyst in catalytic decomposition of dye Rhodamine B in water under light irradiation:

[0069] 500 mL of a 25 mg / L Rhodamine B aqueous solution was prepared, and 50 mg of the CdS / BiOBr composite nanofiber photocatalyst prepared in Example 2 was immersed in the solution. The solution was first stirred for 60 min in the dark to establish an adsorption-desorption equilibrium between Rhodamine B and the CdS / BiOBr composite nanofiber photocatalyst. The solution was then exposed to light for 30 min, and the ultraviolet absorbance of Rhodamine B was measured at 10-min intervals to calculate the degradation efficiency.

[0070] like Figure 4 As shown in the figure, after reaching adsorption equilibrium in the dark environment for 30 minutes, the adsorption rate of Rhodamine B by CdS / BiOBr composite nanofiber photocatalyst was 59%, indicating that the large specific surface area of ​​the nanofiber membrane makes it have a strong adsorption capacity for dyes and organic pollutants. After 30 minutes of illumination, the degradation rate of Rhodamine B by CdS / BiOBr composite nanofiber photocatalyst was 99.7%. The photocatalytic degradation process conforms to the first-order kinetic model, and the degradation rate constant is 0.158min -1 .

[0071] Example 5

[0072] Stability test of CdS / BiOBr composite nanofiber photocatalyst:

[0073] 250 mL of 25 mg / L Rhodamine B aqueous solution was prepared and numbered as solutions 1 to 6. 20 mg of the CdS / BiOBr composite nanofiber photocatalyst prepared in Example 2 was immersed in solution 1. First, it was stirred for 60 minutes in the dark, and then the light was irradiated for 30 minutes. The ultraviolet absorbance of Rhodamine B was sampled and tested, and the degradation rate was calculated. Then the CdS / BiOBr composite nanofiber photocatalyst was taken out and washed with 50 mL of deionized water for 3 times. After the surface water was dried, it was immersed in solution 2 for the experiment. The operation process was the same as above. The above process was repeated for a total of 6 cycles.

[0074] like Figure 5 As shown, the degradation rate of Rhodamine B by CdS / BiOBr composite nanofiber photocatalyst decreased from 99.7% to 89.2% after 6 cycles, proving that CdS / BiOBr composite nanofiber photocatalyst has good reusability.

[0075] Comparative Example 1

[0076] The preparation methods of hydrothermally growing BiOBr and CdS nanoparticles on the surface of PAN nanofiber membrane are as follows:

[0077] 3.5g polyacrylonitrile (PAN) was dissolved in 20g N,N-dimethylformamide (DMF) and stirred to obtain a transparent and viscous spinning solution. The spinning solution was loaded into a plastic syringe for electrospinning. The applied voltage was 15kV, the needle tip was 15cm away from the receiver, the roller speed was 800RPM, the injection pump flow rate was controlled to be 1.2mL / h, and the PAN nanofiber membrane was collected on the aluminum foil of the receiver.

[0078] 2.5mmol Bi(NO3)3·5H2O and 100mg PAN nanofiber membrane were dispersed in 40mL ethylene glycol (EG), and then 10mL ultrapure water dissolved with 2.5mmol KBr was added to the solution, and the mixture was transferred to a 100mL polytetrafluoroethylene-lined autoclave for hydrothermal reaction at 140℃ for 8 hours. After the reaction, it was naturally cooled to room temperature, and the PAN-BiOBr nanofiber membrane was washed 3 times with ultrapure water and ethanol respectively, and dried in an oven at 40℃ for 4h.

[0079] 2mmol of Cd(Ac)2·2H2O was dissolved in 50mL of ultrapure water and stirred for 20min. Then, 2mmol of Na2S·9H2O and the PAN-BiOBr nanofiber membrane prepared in the second step were added to the solution and stirred for 20min. The mixture was transferred to a 100mL polytetrafluoroethylene-lined autoclave and subjected to hydrothermal reaction at 140℃ for 8h. After the reaction, the mixture was cooled to room temperature naturally, and the PAN-BiOBr / CdS nanofiber membrane was washed with ultrapure water and ethanol for 3 times, respectively, and dried in an oven at 40℃ for 12h to obtain a PAN nanofiber membrane-based composite photocatalyst with BiOBr and CdS nanoparticles grown on the surface.

[0080] like Figure 6 The PAN-BiOBr / CdS nanofiber membrane with BiOBr and CdS nanoparticles grown on the surface after two hydrothermal reactions was subjected to light irradiation for 30 minutes. The degradation rate of Rhodamine B was 69.2% for the first time, 41.6% after two cycles, and 33.1% after three cycles.

Claims

1. A CdS / BiOBr composite nanofiber photocatalyst, wherein: BiOBr nanoparticles are loaded in the nanofibers and / or on the surface of the nanofibers, CdS nanoparticles are formed on the BiOBr exposed on the surface of the nanofibers, and the BiOBr nanoparticles and the CdS nanoparticles form a CdS / BiOBr heterojunction.

2. The CdS / BiOBr composite nanofiber photocatalyst according to claim 1, wherein: The diameter of the BiOBr nanoparticles is 200 nm to 2 μm; and / or The diameter of the CdS nanoparticles is 200 nm to 10 μm; and / or The diameter of the nanofiber is 500nm to 5μm; and / or The nanofiber is polyvinylidene fluoride nanofiber or polyacrylonitrile nanofiber.

3. The CdS / BiOBr composite nanofiber photocatalyst according to claim 1 or 2, wherein: Relative to the total weight of the CdS / BiOBr composite nanofiber photocatalyst, the weight ratio of the BiOBr nanoparticles is 2% to 30%, and the weight ratio of the CdS nanoparticles is 0.5% to 50%; and / or The CdS / BiOBr composite nanofiber photocatalyst is in the form of a nanofiber film.

4. The CdS / BiOBr composite nanofiber photocatalyst according to claim 3, wherein: The thickness of the nanofiber membrane is 500nm~50μm.

5. A method for preparing the CdS / BiOBr composite nanofiber photocatalyst according to any one of claims 1 to 4, comprising the following steps: (1) dissolving a bismuth salt in an organic solvent to prepare a solution A, and dissolving a bromide in deionized water to prepare a solution B; then, mixing the solution A and the solution B to obtain a mixed reaction system, and stirring to generate BiOBr nanoparticles; adding a polymer thereto, and stirring and mixing to form a transparent, viscous, and homogeneous spinning solution; (2) spinning the spinning solution obtained in step (1) to obtain a BiOBr nanofiber membrane; (3) Dissolving cadmium salt in deionized water to prepare solution C, and adjusting the pH value to 3-6; dissolving sodium sulfide in deionized water to prepare solution D, and adjusting the pH value to 10-12; using solution C and solution D to precipitate and grow CdS nanoparticles on the BiOBr nanofiber membrane through a continuous ion layer adsorption reaction method to obtain a CdS / BiOBr composite nanofiber photocatalyst.

6. The method for preparing CdS / BiOBr composite nanofiber photocatalyst according to claim 5, wherein: The volume ratio of solution A to solution B in forming the mixed reaction system is 20:1 to 100:1; and / or The molar ratio of Bi in solution A to Br in solution B to form the mixed reaction system is 1:1; and / or The molar concentration of Bi in solution A is 0.005 to 1 mol / L; and / or The molar concentration of Br in solution B is 0.1 to 10 mol / L; and / or The bismuth salt is one or more selected from bismuth nitrate, bismuth chloride, bismuth citrate, bismuth salicylate, bismuth acetate and bismuth oxalate; and / or The bromide is one or more selected from potassium bromide or sodium bromide; and / or The organic solvent is an organic solvent miscible with water; preferably N,N-dimethylformamide or N,N-dimethylacetamide; and / or The polymer is polyvinylidene fluoride or polyacrylonitrile; and / or The content of the polymer is 8 wt% to 20 wt% relative to the total weight of the spinning solution.

7. The method for preparing CdS / BiOBr composite nanofiber photocatalyst according to claim 5 or 6, wherein: The method steps in step (2) are as follows: The spinning solution is added into a syringe and connected to the electrospinning needle through a pipeline. The positive electrode of the high-voltage power supply is connected to the electrospinning needle as the spinning end. The ground electrode of the high-voltage power supply is connected to a rotating roller covered with aluminum foil as the receiving end. A micro-injection pump is used to control the flow rate of the spinning solution, and voltage is applied for electrospinning. The BiOBr nanofiber membrane is collected at the receiving end.

8. The method for preparing CdS / BiOBr composite nanofiber photocatalyst according to claim 7, wherein: In step (2), the flow rate of the spinning solution is 0.5 to 2 mL / h; the spinning voltage is 10 to 25 kV, the distance between the spinning end and the receiving end is 10 to 30 cm; the rotation speed of the rotating roller is 100 to 2000 rpm; and / or The cadmium salt is selected from cadmium acetate, cadmium chloride and cadmium nitrate; and / or The molar concentration of cadmium in solution C is 0.05 to 0.2 mol / L; and / or The molar concentration of the sodium sulfide solution is 0.025-0.2 mol / L.

9. The method for preparing a CdS / BiOBr composite nanofiber photocatalyst according to any one of claims 5 to 8, wherein: The reagent for adjusting the pH of solution C is hydrochloric acid, acetic acid or sulfuric acid; and / or The reagent for adjusting the pH of solution D is sodium hydroxide solution, potassium hydroxide solution or ammonia solution.

10. The method for preparing a CdS / BiOBr composite nanofiber photocatalyst according to any one of claims 5 to 9, wherein: The operation steps of the continuous ion layer adsorption reaction (SILAR) method in step (3) are: (a) immersing the BiOBr nanofiber membrane obtained in step (2) into solution C to adsorb cadmium ions on the surface for 30 to 180 seconds; (b) taking out the BiOBr nanofiber membrane and immersing it in deionized water for cleaning, preferably immersing it in 50 to 500 mL of deionized water for cleaning for 30 seconds; (c) The BiOBr nanofiber membrane was taken out and immersed in solution D for in situ growth of CdS for 30 to 180 s; (d) taking out the BiOBr nanofiber membrane and immersing it in unused deionized water for cleaning, preferably immersing it in unused 50 to 500 mL of deionized water for cleaning for 30 seconds; (e) The above four steps (a) to (d) are performed sequentially as one cycle, and the number of cycles is 3 to 50 to obtain a CdS / BiOBr composite nanofiber photocatalyst.

Citation Information

Patent Citations

  • Preparation method of photoelectric thin-film material based on BiOBr / CdS heterojunction

    CN104659157A

  • Bismuth-oxybromide-cadmium sulfide nano composite photocatalyst and preparation method thereof

    CN107519903A

  • Photocatalyst supported micro-nano-composite fiber material loaded and preparation method thereof

    CN109126881A

  • Electrostatic spinning photocatalytic nanofiber membrane as well as preparation method and application thereof

    CN117661192A